Research-based theatre across disciplines: A relational approach to inquiry. Issue 1 (1st July 2021) - Shigematsu, Tetsuro; Cook, Chris; Belliveau, George; Lea, Graham W.
Research-based theatre (RbT) is an innovative research methodology that draws on theatre practices and conventions to engage in and share research. It is an inherently collaborative and relational methodology, inviting research participants, artists and researchers to take part in embodied data generation, analysis and knowledge-exchange activities. This methodology encompasses writing, rehearsing and performing a research-based monologue, scene or play. In this article, the authors share three recent examples from interdisciplinary projects where researchers and artists engaged with different communities to dramatize data using an RbT methodological approach. To add to literature in the field, the authors consider their experiences leading RbT projects in three disparate fields: theatrical, social and therapeutic. The authors explore the question of how RbT transforms relationships and how relationships transform RbT.